2012
DOI: 10.1111/j.1365-2966.2012.20410.x
|View full text |Cite
|
Sign up to set email alerts
|

X-ray characteristics and the spectral energy distribution of AE Aquarii

Abstract: Using data from contemporaneous observations with Chandra and Swift, it is shown that the X‐ray emission below 10 keV is predominantly thermal, characterized by flares and emission lines and dominated by the soft component. The Chandra and Swift X‐ray spectra (EX≤ 10 keV) can be reproduced by multicomponent thermal emission models with a time‐averaged X‐ray luminosity of LX∼ 1031 erg s−1. The pulsed 33‐s soft X‐ray emission below 10 keV is confirmed in both the Chandra and Swift data sets. The epoch of pulse m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(67 citation statements)
references
References 65 publications
8
59
0
Order By: Relevance
“…These peculiar observational properties make AR Sco a unique system. Although AR Sco could be in the evolutionary stage of the so-called intermediate polar (Bookbinder & Lamb 1987;Patterson 1994;Oruru & Meintjes 2012), of which accretion is the main power source, the absence of accretion features in AR Sco demands another mechanism to explain the observations. It has been suggested that if the dipole magnetic field of a WD is strong enough, it would behave like a WD radio pulsar (Zhang & Gil 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These peculiar observational properties make AR Sco a unique system. Although AR Sco could be in the evolutionary stage of the so-called intermediate polar (Bookbinder & Lamb 1987;Patterson 1994;Oruru & Meintjes 2012), of which accretion is the main power source, the absence of accretion features in AR Sco demands another mechanism to explain the observations. It has been suggested that if the dipole magnetic field of a WD is strong enough, it would behave like a WD radio pulsar (Zhang & Gil 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The nature of the non-thermal emission from AE Aquarii, from radio to VHE gamma-ray gamma-rays, have been investigated in detail by [38], [27] and [39]. It has been shown that episodes of particle acceleration may be associated with the propeller process in AE Aquarii.…”
Section: Figurementioning
confidence: 99%
“…in the white dwarf magnetosphere in AE Aquarii has been investigated by [35] and [39]. It has been shown that huge potentials of the order of V ∼ 3 × 10 12 P −2 33 µ 33 Volt can exist between the white dwarf surface and the light cylinder, which can accelerate charged particles to VHE-TeV energies.…”
Section: Pos(multif15)031mentioning
confidence: 99%
See 1 more Smart Citation
“…This rapidly rotating magnetized WD would mimic the neutron star pulsars as pointed out by Geng et al 24 Another specific example is AE Aquarii, the first white dwarf pulsar (an intermediate polar WD), very fast with a short period P = 33 s, and spinning down at a rateṖ = 5.64 × 10 −14 s/s. The luminosity of this source and the nature of pulse hard X-ray emission detected with SUZAKU space telescope 25,26 can be explained in terms of spin-powered pulsar mechanism 27, 28 and emit detectable high-energy radiation.…”
Section: White Dwarf Pulsarsmentioning
confidence: 99%